2017
DOI: 10.1371/journal.pone.0181048
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study revealed first insights into the diversity and metabolisms of the microbial communities in the sediments of Pacmanus and Desmos hydrothermal fields

Abstract: Currently, little is known about the microbial diversity in the sediments of Pacmanus and Desmos hydrothermal fields in Manus Basin. In this study, Illumina-based sequencing of 16S rRNA gene amplicons and metagenomic analysis were conducted to investigate the microbial populations and metabolic profiles in the sediments from four different regions in Pacmanus and Desmos hydrothermal fields. It was found that Gammaproteobacteria and Thaumarchaeota were the most abundant bacterial and archaeal populations, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…This inference holds true for the hydrothermal vent fields from the Eastern Manaus Basin of Papua New Guinea, from which microbial communities including chemoautotrophic and chemoheterotrophic microorganisms dependent on sulfur, nitrogen, or hydrogen metabolisms have been reported (e.g. Kimura et al, 2003; Meier et al, 2019; Takai et al, 2001; Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…This inference holds true for the hydrothermal vent fields from the Eastern Manaus Basin of Papua New Guinea, from which microbial communities including chemoautotrophic and chemoheterotrophic microorganisms dependent on sulfur, nitrogen, or hydrogen metabolisms have been reported (e.g. Kimura et al, 2003; Meier et al, 2019; Takai et al, 2001; Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…sinensis are moderate, while the habitat of Austinograea sp. is one of the most extreme environments on Earth, where bacterial diversity (7.20–8.27 for Shannon) may be much greater than other marine microbial diversity [ 38 , 49 ]. The highest diversity of microbial communities observed in the gill of Austinograea sp.…”
Section: Discussionmentioning
confidence: 99%
“…Desmos and Pacmas are the two fields in the Manus Basin, where low pH and high concentrations of H 2 S and SO 4 2- were detected [ 37 ]. Other environment data and microbial communities in the sediments of these two sites have been published by Wang et al [ 38 ]. Fresh intestines and gills of E .…”
Section: Methodsmentioning
confidence: 99%
“…Iron oxidizers not only play a role in mineral sulfide alteration, they also expand the carbon fixation capacity of vent systems long after hydrothermal circulation has ceased (Glynn et al, 2006;Li et al, 2017). Chemoautotrophic iron oxidizers have been described from rocks and sediment samples from inactive areas (Emerson and Moyer, 2002;Edwards et al, 2003) More recently, Wang et al (2017) revealed new insights into the operational mechanism of the microbial communities associated with Pacmanus and Desmos hydrothermal sediments. Gammaproteobacteria were the most abundant bacterial populations.…”
Section: Production Of Chemosynthetic Resources On Stable and Inactivmentioning
confidence: 99%